2018
DOI: 10.1111/jam.14043
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of marine-derivedStreptomycessp. UTMC 1334 as a source of pyrrole derivatives with anti-acetylcholinesterase activity

Abstract: This study highlights that exploring new lead anti-AChE compounds may result in discovering novel adjuvant candidates with potency in the treatment of cognitive diseases such as AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…Previous studies had found that peptides prevented cognitive impairment by improving the composition of the gut microbiota and its metabolites [ 61 ]. As we expected, this study found that THPH administration altered gut microbiota diversity in cognitive impairment mice, including increasing the abundance of Actinobacterota , which produced metabolites with anti-AchE activity [ 62 ]. THPH treatment also increased the abundance of probiotics, such as Lactobacillus reuteri and Prevotellaceae UCG-001 , which had the effects of regulating neural behavior and improving cognitive function, and produced metabolites that participated in the hosts’ lipid metabolism to maintain the brain function [ 63 , 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 75%
“…Previous studies had found that peptides prevented cognitive impairment by improving the composition of the gut microbiota and its metabolites [ 61 ]. As we expected, this study found that THPH administration altered gut microbiota diversity in cognitive impairment mice, including increasing the abundance of Actinobacterota , which produced metabolites with anti-AchE activity [ 62 ]. THPH treatment also increased the abundance of probiotics, such as Lactobacillus reuteri and Prevotellaceae UCG-001 , which had the effects of regulating neural behavior and improving cognitive function, and produced metabolites that participated in the hosts’ lipid metabolism to maintain the brain function [ 63 , 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 75%
“…to improve AD hallmarks, were evaluated. Compounds were able to protect SH-SY5Y neuroblastoma cells from H 2 O 2 -induced oxidative injury by activating the nuclear factor E2-related factor (Nrf2) [ 106 ].…”
Section: Main Textmentioning
confidence: 99%
“…Streptomyces sp. UTMC 1334 also known as Streptomyces lateritius was shown to produce pyrroles and other metabolites with AChE inhibitory activity (Almasi et al 2018 ). Astrocytes protect the nervous system from oxidative damages caused by ROS generation (Drukarch et al 1998 ).…”
Section: Neuro- and Cardioprotective Effects Of Bacterial Extractsmentioning
confidence: 99%